Effect Of Massage Therapy Towards Weight Gain On Stunting Toddlers - Ayu Mutia Lestari; Yulinda Laska; Erika Fariningsih (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2022)
Stunting is a chronic nutritional problem occurringin toddlers, characterized by shorter height compared to children of their age. Massage therapy is known to providevarious benefits such as increasing endurance, increasing body weight, stimulating the Vagus nerve, increasing breast milk production, overcoming stomach pain, and improving sleep quality. This research employed Quasi-Experiment method with Two Groups Pre-test and Post-test design, by observing and giving treatment for 14 days. The research involved 20 stunting toddlers in Tanjung Riau, Batam as the samples. The research results revealed that there was an effect of giving massage therapy on weight gain in stunting toddlers. The Independent Sample T-test obtained a significant p-value of 0.033 (P < 0.05).Therefore, it can be concluded that there is an effect of giving massage therapy on weight gain in stunting toddlers.